Grand rights and opera reuse today - Cuntz, Alexander (Economic research working paper series ;, 2020)
This article studies the economic role of grand rights in the incentives to stage and reuse works from the opera canon. It complements previous research on the incentives to create new opera (Giorcelli and Moser, 2020) in the way it looks at copyright taxing availability and follow-on creativity around works. Based on a unique dataset of global opera performances, we find that changes in copyright status increase the number of total performances individual works receive on stage once copyright expires. Moreover, we provide preliminary evidence on chilling, long-term effects of status around premiering operas and revivals at the beginning of the copyright term. Based on these findings, we discuss limitations of the study and novel options for copyright policy frameworks.